DISTRIBUSI TANGGUNGJAWAB PENDIDIKAN ANAK DALAM KELUARGA PADA PEREMPUAN YANG BERPROFESI SEBAGAI PENDIDIK - Hadi Pajarianto (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
Child education is family, nation and country's future investment. Sometimes the women's role is too dominant in child education, Since women are known as the first madrasah (School) for children. This research aims to explore how the distribution of responsibility in child education on women working as educator. This research is a descriptive qualitative reserach with case study approach. The researvh subject is 5 women who works as educator, the data was collected with few techniques, which is observation, indepth interview, and documentation, and the main instrument on this research is the researchers. The data analysis consists of data reduction, data study and verification or conclusion withdraw. The results show that the distribution of child education duty is done by functional equality and ta'awun principal. A father is the chief of a family. Husband and wife shares the same responsibility, but has to be dobe situationally, where the wife and husband can take decision by communicating each other. The contribution of this research is to build the equality of man and woman in educating children. The status quo is women tend to have more responsibility thus men suppose to be the support in lightening the responsible.